Pengaruh Kurs Rupiah Terhadap Indeks Harga Saham (Studi Pada Indeks Saham Syariah Indonesia Periode 2011-2013) - Saputra, Imam Dwi; Herlambang, Leo (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Sensitivity of stock market is appeared when the domestic currency exchange rate fluctuations happened. Uncontrolled currency fluctuations will affect the performance of capital market entities which have an impact on stock price movement. This thesis is to determine the effect of exchange rate on ISSI stock price index in the 2011-2013 periods.This thesis uses a quantitative approach to analyze secondary data whichrepresented by exchange rate and ISSI stock price index. Those values are monthly data over the period 2011-2013. This thesis also uses a significance level of 5%.The regression result in this thesis indicates that the exchange rate variable has a significant effect partially on ISSI stock price index in the 2011-2013 periods.